The linguistic turn and social psychology - Desmond Painter; Wilhelmina Theron (Acta Academica, 2001)
This article investigates some of the implications of the linguistic turn in modern philosophy for the development of social psychology. The linguistic turn, according to which language does not primarily mirror reality or our experience but is co-constructive thereof, gave rise to productive developments in social psychology. Wittgenstein’s insight that the meaning of words depends on their use value in specific language games made it possible to see social cognition as an interactive and social achievement, rather than as a selfenclosed mental process merely directed at the social environment. Post-structuralist developments like those of Derrida and Foucault, based on the structuralist linguistics of De Saussure, make the psychological subject, experience, social institutions and knowledge products of more fundamental textual processes. Despite contradictions these approaches underlie the development of what may be called a discursive social psychology: a discipline focusing on the different discursive aspects of social psychological life, which refuses to restrict that life to individual levels of analysis.